2009
DOI: 10.1111/j.1742-6723.2009.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Convulsive and non‐convulsive status epilepticus: An emergency medicine perspective

Abstract: Status epilepticus (SE) is divided into convulsive and non-convulsive types; both are associated with significant morbidity and mortality. Although convulsive SE is easily recognized, non-convulsive SE remains an elusive diagnosis as physical signs are varied and subtle. Successful management depends on a comprehensive approach that involves diagnostic testing and pharmacological interventions while ensuring cerebral oxygenation and perfusion at all times. There are a limited number of well-designed studies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 111 publications
1
44
0
1
Order By: Relevance
“…19) NCSE is defined as a change in behavior and/or mental process from the baseline associated with ongoing seizure activity or continuous epileptiform discharges on EEG in the absence of convulsive symptoms. 2,16,20) Epileptic activity causes increased metabolic demand in the involved cortex, which is accompanied by temporarily increased regional cerebral perfusion. 6,8) Since PLEDs are one of the EEG patterns in patients with NCSE, 2,9) the pathophysiology of``ictal'' hyperperfusion could be similar to that observed in our case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19) NCSE is defined as a change in behavior and/or mental process from the baseline associated with ongoing seizure activity or continuous epileptiform discharges on EEG in the absence of convulsive symptoms. 2,16,20) Epileptic activity causes increased metabolic demand in the involved cortex, which is accompanied by temporarily increased regional cerebral perfusion. 6,8) Since PLEDs are one of the EEG patterns in patients with NCSE, 2,9) the pathophysiology of``ictal'' hyperperfusion could be similar to that observed in our case.…”
Section: Discussionmentioning
confidence: 99%
“…1) Mortality is reported to be mainly dependent on underlying etiology and age, but NCSE carries a poor prognosis so prompt diagnosis and subsequent treatment is important. 2,16,20) SPECT and ultrasonography can clearly demonstrate the hyperperfusion state, but cannot detect neuronal function, especially neuronal excitability. In contrast to hyperperfusion after CEA, hyperperfusion is delayed after STA-MCA anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review by Maganti et al (8) on NCSE, they reported that IV benzodiazepines could be given as first-line therapy followed by IV phenytoin, phenobarbital, or valproic acid. Levatiracetam has become a commonly used agent for SE at emergency departments, particularly for pediatric patients (11). In a retrospective study conducted by Osorio et al (12), they found that the epileptiform waves of refractory SE patients who were administered IV 10 mg diazepam were suppressed on EEG.…”
Section: Discussionmentioning
confidence: 99%